Ab initio prediction of strong interfacial bonding in the Fe|Al bimetallic composite system. (1st March 2020) - Czelej, Kamil; Kurzydłowski, Krzysztof J.
Abstract: Atomic-scale calculations were used to investigate the formation of interfacial bonds in the Fe|Al bimetallic composite system. The results indicate that chemical bonds at pristine Fe|Al interface display more covalent character than constituent materials resulting in enhanced interface strength. Such an interface exhibits large cohesive energy exceeding significantly the value of bulk aluminum. The effect of two technologically relevant solute elements, i.e. carbon and magnesium on the interface strength was analyzed. Our robust yet simple computational model can be used to predict the most efficient combination of steels and aluminum alloys for cold pressure welding, leading to strong interfacial bonding. Graphical abstract: Image, graphical abstract